Infeksi Menular Seksual Sebagai Faktor Resiko Independen pada Kejadian Stunting di Makassar - Mile, Murshalina; Haruna, Nadyah; Palincoi, Najamuddin; Irnawati, Risma; Fatmawati, Fatmawati (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2026)
Background: Stunting remains a pressing global nutritional problem and a significant public health concern in Indonesia. Multiple maternal factors, including sexually transmitted infections (STIs), inadequate nutrition, and poor environmental sanitation, have been linked to impaired fetal growth. However, the relationship between maternal STIs and childhood stunting is not well explored. Objective: This study aimed to determine the association between maternal STIs and the incidence of stunting among infants. Methods: A case-control study was conducted from October 2023 to January 2024 at Kassi-Kassi Primary Health Center, Makassar, Indonesia. A total of 30 participants were enrolled using total sampling, comprising 15 case samples (mothers of stunted infants) and 15 control samples (mothers of non-stunted infants). Data were obtained through structured interviews and medical records and analyzed using Chi-square tests to estimate odds ratios (OR) and 95% confidence intervals (CI). Results: The prevalence of maternal STIs (Hepatitis B, HIV, and syphilis) was 50%. Mothers with positive STI status had a significantly higher risk of delivering stunted infants (73.3% in the case group vs. 26.7% in the control group), with an OR of 7.56 (95% CI: 1.50–36.15; p = 0.014). Conclusion: Maternal STIs are significantly associated with an increased risk of stunting in infants. These findings underscore the importance of routine STI screening and preventive interventions during antenatal care to reduce the risk of childhood stunting.